Economic analysis of projects - Squire, Lyn (IBRD WashingtonUS, 1975)
Provides a broad review of the basic notions of cost-benefit analysis. Gives an explanation of the nature of shadow prices and how they can be derived, in priciple, so as to reflect appropriately a wide range of economic conditions and value judgements concerning basic policy objectives pertaining to growth and distribution. Reviews various approximate methods that may be feasible and appropriate for estimating these shadow prices in practice, depending on data available and circumstances in a particular country.